Metallodrugs with antibacterial activity and their incorporation into nanocellulose membranes for wound healing applications - Gomes, Adriana Catarina da Costa (2023)
Wounds have a significant impact on society, not only on those who suffer from them but also on the health care system. Moreover, wounds do not always follow the expected healing process. The incidence of complications, such as infections, can inhibit wound healing and increase the cost of health care. Therefore, wound dressings emerge as a possible solution since they are crucial in promoting wound healing. In an increasingly environmentally conscious society, biopolymers-based wound dressings are becoming more eminent because of their abundance, renewable character, exudates’ absorption capacity, and non-citotoxicity. Cellulose is an example of a widely studied polysaccharide, being increasingly used in wound healing applications. In particular, bacterial cellulose (BC) has a unique morphology and unique physicochemical, mechanical, and biological properties. In addition, BC can be modified and functionalized in order to have better performances. Moreover, bacterial cellulose has a nanofibrillar structure that provides ideal conditions for wound healing, and BC-based materials can act as drug delivery systems due to their ability to incorporate and release bioactive molecules. On the other hand, antibiotic resistance is one of the biggest threats to global health since it is reducing the ability to treat common infectious diseases. Metallodrugs with antibacterial activity emerge as a possible alternative to antibiotics. These pharmacologically active metal complexes display new properties and might have enhanced biological activity due to the synergistic combination between the ligands and the metal. Besides, metallodrugs possess different geometries and threedimensional structures that are generally associated with higher clinical success rates. Thus, the main goals of this work were to synthesize and characterize metallodrugs with antibacterial activity, and to incorporate them into BC membranes for wound healing applications. Hence, this work included the synthesis and characterization of cobalt(II), copper(II), nickel(II), and zinc(II) complexes of levofloxacin and ciprofloxacin, in the presence and absence of N-donor ligands. All fourteen complexes characterized exhibited antibacterial activity against Staphylococcus aureus. One of them was successfully incorporated into BC membranes, increasing their thermal stability. A rapid release profile, suitable for topical administration, was obtained. Therefore, this work serves as a good starting point for the scientific community, but it also might be a future solution for a problem that affects millions of people.